Rethinking OER and their Use: Open Education as Bildung - Deimann, Markus; Farrow, Robert (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
Despite the recent increases of interest in open education, notably in massive open online courses (MOOCs) (Fini, 2009), it has been continuously asserted that this form of social knowledge production lacks a philosophical or theoretical foundation (Vandenberg, 1975). Similar accusations have been made with respect to distance education, such as being slow to engage with critical debates in theory and research (Evans & Nation, 1992). In a similar vein, Danaher, Wyer, and Bartlett (1998) claim that researchers in open and distance learning tend to draw on too narrow a range of theoretical resources in their research. Given the considerable rise of open education over recent years, these critical appraisals urge us to expand theoretical approaches and refine our understanding of evolving pedagogical and technological relations (cf. Bell, 2011). In this paper, we contribute to debates surrounding open education and open educational resources by introducing the concept of Bildung (self-cultivation, self-realization) as a powerful reflective tool and framework for approaching open education. We will elaborate on the potentials of Bildung by reviewing the history of the concept and exploring the extent to which Bildung can provide open education with a theoretical framework. Our focus is not exclusively on open educational resources (OER): We follow other commentators (Mackey & Jacobson, 2011, p. 62; cf. Weller, 2011) who argue that ‘openness’ in education necessarily shifts the focus from content (OER) to practices (OEP) that are necessary for the use of that content. We also argue that the beliefs and values associated with Bildung – including autonomy, critical reflection, inclusivity, and embracing the potential for self-development – are suitable for providing a theoretical framework for open education as well as providing a critical lens through which to assess contemporary models of education (e.g., Liessmann, 2006).